Konglish as Cultural Practice: Reconsidering the English Language in South Korea - Joseph Sung-Yul Park (Cranmore Publishing, 2021)
English in South Korea, where the language is highly emphasized as a necessary language for the age of globalization, continues to have limited use within the country's dominant Korean language monolingualism, despite the fact that localized forms of linguistic resources originating from English permeate everyday communication. This sociolinguistic characteristic has led to problems for concepts that aim to provide a typology of new Englishes by identifying them in terms of distinct varieties - including the notions of English as second language/English as foreign language, inner/outer/expanding circles, and English as lingua franca. In this paper, I argue that a proper understanding of English in South Korea requires that we move away from such variety-based approaches, instead viewing language as practice embedded in speakers' communicative activity in social context. For this purpose, I discuss the case of Konglish, a term that pejoratively refers to English as used by Koreans. While previous studies have rightly argued that expressions condemned as Konglish should be seen as legitimate localized uses of English, here I focus on how Konglish does not represent a variety but a cultural practice, in which Koreans draw upon whatever resource available to them in making communicative action, and through which Koreans conceptualize their position in the global world. Based on this discussion, I argue that research on English as a global language should move beyond the varieties-based approach that focuses on typologies of Englishes to ask more fundamental questions about the nature of language itself.